PRODUCTION OF PROTEIN AND GALACTOMANNAN AS FUNCTIONAL FOOD INGREDIENTS FROM COCONUT SKIM WITH MEMBRANE TECHNOLOGY - Wiantama, Joshua
Coconut is one of the largest agricultural commodities in Indonesia which has benefits from all parts of the plant. One of the products produced from coconut is pure coconut oil (VCO). In the process of making VCO, side products are also produced in the form of coconut skim and coconut cream. Coconut skim is a byproduct that still contains rich protein and galactomannan in carbohydrates which can be further processed to obtain greater economic value. The coconut skim used has a protein content of 1.14%-per oil with 1.46%-per 100 grams. In the process of producing protein and galactomannan from coconut skim using membrane technology, temperature variations are carried out on microfiltration membranes (MF) of 50 and 70oC at a pressure of 1 bar, ultrafiltration membranes (UF) and process variations involving the deamidation process. The temperature variation obtained by dasil with a temperature of 70 oC had a lower protein rejection value, more oil was retained on the MF membrane. After the MF(PP) membrane process was continued with the UF (PVDF) membrane, in both variations the protein rejection values were not much different, namely 85.4% (50oC) and 83.5% (70oC). There are 4 different variations of the process involving deamidation in the MF process (70oC) and UF, without deamidation, deamidation before MF, after MF and after UF. The deamidation process carried out in this variation of the process has a significant influence on membrane flux and protein solubility test results. The protein solubility value without deamidation was obtained at 78.9% while the variation in the process with deamidation was greater than 80%. Apart from that, statistical analysis shows that in this process temperature variations and process variations with deamidation have a significant effect on the levels of protein and galactomannan produced. Products resulting from various processes using deamidation are more popular as functional food ingredients due to changes in the characteristics of protein and galactomannan, one of which is increased solubility making it easier to apply in functional food products.